Twins, Albinos and Vanishing Prisoners: A Mozambican Theory of Political Power - Granjo, Paulo (Department of Dutch and South African Studies, Faculty of English, 2010)
In coherence with old ethnographic references, twins and albinos are still seen, in southern Mozambique, as the result and the cause of cosmic calamities. They were struck by lightning bolts inside their pregnant mothers, and they will dry the land unless they are buried under special conditions, or just ‘vanish’ from the Earth. The special conditions imposed on their lives and deaths were extrapolated, in recent decades, to depict an unexpected category of people: the political prisoners who vanished from colonial jails, or were sent by the post-indepen ence state to ‘re-education camps.’ However, this was not the case of the ‘unproductive’ urbanites who disappeared under domestic exile in the Niassa region. The beliefs about twins and albinos were used in order to express a local moral statement about political power: it is socially threatening to jeopardise the established power; but it is illicit, for a legitimate power, to take unfair decisions about the people under its responsibility.
Keywords: Africa; albino's; land dryers; Mozambique; Operation Production; political prisoners; rain rituals; social contract; twins